PdII‐Catalyzed Spiroannulation of Cyclic N‐Sulfonyl Ketimines with Aryl Iodides through C–H Bond Activation. Issue 28 (26th July 2017) - Reddy, K. Nagarjuna; Rao, M. V. Krishna; Sridhar, B.; Reddy, B. V. Subba
Abstract : A new strategy has been developed for the synthesis of spirofluorenyl benzosultams through the annulation of aryl iodides with cyclic N ‐sulfonyl ketimines. This method uses a readily available Pd II catalyst for the activation of aryl C–H bonds to facilitate the annulation process. Pd is cheaper than other transition metal catalysts commonly used for the C–H activation, such as Ir and Rh. This approach leads to the synthesis of biologically relevant spiro‐benzosultams in a single‐step process. Abstract : A new strategy has been developed for the synthesis of spirofluorenyl benzosultams through the annulation of aryl iodides with cyclic N ‐sulfonyl ketimines. This method uses a readily available Pd II catalyst for the activation of aryl C–H bonds, and leads to the synthesis of biologically relevant spiro‐benzosultams in a single step.